Acute effects of joint manipulation on myofascial trigger point pain: A randomized clinical trial: Effects of joint manipulation on trigger point pain - D. Gregorio, Matheus; H. Dias, Yves; U. Koeke, Paulo; D. Telles, Jonathan (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: Myofascial trigger points are considered one of the main myofascial pain syndromes in the neck, characterized by regional pain and muscle tenderness with the presence of hypersensitive nodules in the muscle band. Several techniques are tested for controlling this pain, one of the options being joint manipulation. These techniques can be used either individually or even combined, in order to elicit neurophysiological responses related to pain processing and inhibition. Objectives: Evaluate the immediate effects of combined joint manipulation versus isolated application of this technique on the pressure pain threshold in individuals with trigger points in the upper trapezius fibers. Methods: Thirty participants aged between 18 and 30 years with myofascial trigger points in the upper trapezius muscle were distributed into three groups: cervical manipulation, thoracic manipulation, and combined manipulation. The visual analog scale and pain threshold were measured pre- and post-intervention in the upper trapezius muscle. Results: The results showed a significant difference between groups for pain (p=0.009), but there was no difference between groups for pressure pain threshold. Other studies have already shown significant effects of joint manipulation on pain and pressure pain threshold in individuals with myofascial pain. The combination of interventions that have neurophysiological responses related to pain inhibition has superior effects compared to local response techniques. Conclusion: It was concluded that cervical joint manipulation combined with thoracic manipulation was more effective in reducing myofascial trigger point pain in the trapezius muscle than cervical or thoracic manipulation applied in isolation. There was no difference in relation to the pressure pain threshold.